Development Characteristics of Shale Lithofacies in the Longmaxi Formation and their Main Controlling Factors in the Changning Area, South Sichuan Basin, SW China - Tang, Qingsong; Zhou, Lu; Chen, Lei; Tan, Xiucheng; Wang, Gaoxiang (Frontiers in Earth Science, 2021)
Based on core observations, thin sections, X-ray diffraction (XRD), and seismic data, the lithofacies types in the organic-rich Longmaxi shale (Lower Silurian) in the Changning area of the southern Sichuan Basin were identified. The factors controlling the spatial variations in the shale lithofacies and the influences of the shale lithofacies on shale gas development were also analyzed. Results indicate that there are seven main types of shale lithofacies in the Long11 sub-member of the Longmaxi Formation, including siliceous shale (S-1), mixed siliceous shale (S-2), carbonate-rich siliceous shale (S-3), clay-rich siliceous shale (S-4), carbonate/siliceous shale (M-1), mixed shale (M-2), and argillaceous/siliceous shale (M-4). A vertical transition from the carbonate shale association + mixed shale association at the bottom of the sub-member to a siliceous shale association and mixed shale association + siliceous shale at the top generally appears in the Long11 sub-member. The shale lithofacies of the Long11 sub-member also laterally change from the central depression (low-lying area) to the geomorphic highland in the east and west parts of the Changning area. The spatial variations in shale lithofacies in the Long11 sub-member of the Changning area were mainly controlled by palaeogeomorphology and relative sea level. The geomorphic highland area is dominated by carbonate-rich siliceous shale and mixed siliceous shale, but the depression (low-lying area) is mainly dominated by mixed siliceous shale and argillaceous/carbonate shale.